Działania podejmowane przez przedsiębiorstwa w celu zwiększania zaangażowania pracowników (studium empiryczne) - Urbaniak, Maciej (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The purpose of this paper is to present the results of the field research which were concentrating on the identification of the most frequently implemented activities by companies for the commitment of human resources to the effective improvement of management system. The results of research indicate that the companies operated on Polish market to increase employees commitment mostly introduced such activities like the introduction of clear system's documents (procedures, instructions), organizing of obligatory post-training, improvement of safety of work-conditions, possibility of ideas. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1177, s. 48-56